Review Article: Drug-Related Problems in Hypertensive Patients in Pharmaceutical Practice - Agustiani, Eti; Marasabessy, Keysha Nabilla Putri; Dwiyanti, Dhea Syafitri; Mutthoimah, Ulfatul; Ulya, Tuhfatul (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Hypertension is a chronic disease with a high global prevalence and often requires combination therapy, which increases the risk of Drug-Related Problems (DRPs). This review aims to identify the types of DRPs, the most frequently implicated medications, causative factors, and pharmaceutical interventions based on various studies conducted in hypertensive patients. The literature review results indicate that common DRPs include drug interactions, ineffective therapy, the need for additional therapy, adverse drug reactions (ADRs), and inappropriate medication selection. Amlodipine, candesartan, valsartan, beta-blockers, and diuretics are among the medications most frequently associated with DRPs. Polypharmacy, non-adherence, comorbidities, and inadequate monitoring are the main contributing factors. Pharmaceutical interventions such as medication review, therapy monitoring, patient counseling, and adherence to clinical guidelines have been shown to be effective in reducing DRPs. The role of pharmacists is crucial to ensure the safety and effectiveness of hypertension therapy.